A preliminary study on online data privacy frameworks - Rao A.A.; Chen L.F.; Dhillon J.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Social networking (online); Websites; Malaysians; Online data; online data privacy frameworks; Online environments; Online identity; Online privacy; Privacy frameworks; Privacy infringement; Data privacy